Analysis Of The Priority Handling Of Enveromental Drainage Construction Project At Dinas Pekerjaan Umum Dan Penataan Ruang Banjarbaru City - Achmad Rizani; Aqli Mursadin (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
Flood is one of the main problems of big cities in Indonesia, including Banjarbaru City. This is often caused by the not supportive existing drainage capacity when compared to the increasing of crowded urban conditions and reduced green open space. Handling of drainage including rehabilitation is necessary so that drainage can function properly as expected. On the other hand the Banjarbaru City Government has a limited budget each year that can be disbursed for drainage handling. The purpose of this thesis is to analyze criteria and subcriteria that are important in determining the priority of drainage handling. The ANP (Analytic Network Process) method is analyzed using the criteria in the Minister of Public Works regulation number 12/PRT/M/2014 tentang Penyelenggaraan Sistem Drainase Perkotaan to determine priorities for handling environmental drainage with important criteria, namely aspects of inundation, economic loss, social disruption and government facilities, loss of disturbance. transportation, loss to residential areas, and loss of personal property rights. Based on these 6 criteria, priorities for handling environmental drainage in Banjarbaru City are determined. Furthermore, an analysis is carried out to evaluate the priority of the choices that occur. This study suggests to decision makers that ANP can be used to analyze drainage management priorities in Banjarbaru City. This research focuses on variables consisting of criteria or considerations which form the background for priorities in handling the environmental drainage system in Banjarbaru City. The primary data results obtained from the field survey were followed by analysis using the ANP method with data tabulation calculations and assisted by Super Decisions software to determine the priority scale for handling environmental drainage in Banjarbaru City. The treatment priority scale in the Super Decisions software, the data of which is based on field survey results and data tabulation calculations, found that there are several locations that have a large priority scale but treatment has not been carried out due to several factors that are not contained in Minister of Public Works Regulation 12/PRT/M/2014 concerning Implementation of Urban Drainage Systems.